ANTI-DIARRHEAL ACTIVITY OF THE LEAF EXTRACTS OF DANIELLIA OLIVERI HUTCH AND DALZ (FABACEAE) AND FICUS SYCOMORUS MIQ (MORACEAE) - Ahmadu, A. A.; Zezi, A. U.; Yaro, A. H. (African Journal of Traditional, Complementary and Alternative Medicines, 2007)
The leaves of the plants Daniellia oliveri (Fabaceae) and Ficus sycomorus(Moraceae) used in diarrhea treatment in Hausa ethnomedicine of Northern Nigeria were investigated. The study was carried out on parfused isolated rabbit jejunum and castor oil-induced diarrhea in mice. The n-butanol extracts: NBD and NBF (0.16- 3.2mg/ml) caused a dose-dependent relaxation of isolated rabbit jejunum. The acute toxicity test for NBD and NBT in mice established an i.p LD50 of > 4000mg/kg for D. oliveri and 1131.4mg/kg for F. sycomorus. In castor oil-induced diarrhea, 80% protection was observed for D. oliveri at doses of 200mg/kg and 60% protection was observed at 100mg/kg and 50mg/kg respectively. For F. sycomorus 100% protection was observed at doses of 120mg/kg and 60mg/kg, for the n-butanol extract. The antidiarrheal activity was comparable to loperamide 5mg/kg. The result revealed that the extracts have pharmacological activity against diarrhea.